For this post we will explain what is a homotopy of paths.
Source: Topology (2nd Economy Edition)
The book above is a nice introductory book on Topology, which includes a section of introductory Algebraic Topology.
Definition: If f and f’ are continuous maps of the space X into the space Y, we say that f is homotopic to f’ if there is a continuous F: X x I -> Y such that
F(x, 0)=f(x) and F(x,1) = f'(x)
for each x. The map F is called a homotopy between f and f’. If f is homotopic to f’, we write .
If f and f’ are two paths in X, there is a stronger relation, called path homotopy, which requires that the end points of the path remain fixed during the deformation. We write if f and f’ are path homotopic.
Next, we will prove that the relations and are equivalence relations.
If f is a path, we shall denote its path-homotopy equivalence class by [f].
Proof: We shall verify the properties of an equivalence relation, namely reflexivity, symmetry and transitivity.
Given f, it is rather easy to see that . The map F(x,t) is the required homotopy.
F(x,0)=f(x) and F(x,1)=f(x) is clearly satisfied.
If f is a path, then F is certainly a path homotopy, since f and f itself has the same initial point and final point.
Next we shall show that given , we have . Let F be a homotopy between f and f’. We can then verify that G(x,t) = F(x, 1-t) is a homotopy between f’ and f.
G(x,0) = F(x, 1)=f’ (x)
G(x,1) = F(x, 0) = f(x)
Furthermore, if F is a path homotopy, so is G.
G(0,t)=F(0, 1-t) =
Next, suppose that and , we show that . Let F be a homotopy between f and f’, and let F’ be a homotopy between f’ and f”. This time, we need to define a slightly more complicated homotopy G: X x I -> Y by the equation
First, we need to check if the map G is well defined at t=1/2. When t=1/2, we have F(x,2t) = F(x,1)=f'(x) = F'(x,2t-1).
Because G is continuous on the two closed subsets X x [0, 1/2] and X x [1/2, 1] of XxI, it is continuous on all of X x I, by the pasting lemma.
Thus, we may see that G is the required homotopy between f and f”.
G(x,0)=F(x,0) = f(x)
G(x,1) = F’ (x, 1) = f”(x)
We can also check that if F and F’ are path homotopies, so is G.
G(0,t) = F(0, 2t) =
G(1, t)=F'(1, 2t-1) =